Tari Pabbitte Passapu pada Upacara Tradisi Perkawinan di Suku Kajang Dalam - Oktaviani, Ragil Tri (PANTUN: Jurnal Ilmiah Seni Budaya, 2016)
This article tries to reveal the existence of dance pabbitte passapu on pa’buntingang ceremony and dance forms of presentation. The existence of pabbitte passapu dance is believed to be a fertility rite and custom entertainment facilities. However, the presence of dance in the ceremony pa’buntingang pabbitte passapu is already secondary. In a sense, the dancers are not anymore considered as participants but ‘performers to be seen’. Meanwhile, the presentation of the dance, although in the form of a ‘response’, it does not change the structure of dance movement pa!erns pabbitte passapu. The focus of the analysis is the form of dance pabbitte passapu presentation in a traditional marriage ritual ceremony of Inner Kajang. The substance aims to reveal the analytical and descriptive of the subject matter associated with, the presence of dance pabbitte passapu in a traditional marriage ritual ceremony of Inner Kajang In; and the form presentation of pabbitte passapu dance. This article is expected to be contributive to the people of Inner Kajang to maintain the dance arts pabbitte passapu, as well as for the art people to add the inland art discourses in the archipelago.Keywords: Pabbitte Passapu Dance, Kajang Dalam tribe